Kinerja Keuangan PT Waskita Karya (Persero) Tbk - Muhammad Manar Barmawi (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
This research aims to measure the financial performance of PT. Waskita Karya (Persero) Tbk. The analysis was carried out based on the Decree of the Minister of State Owned Enterprise (SOE) Number:KEP-100/MBU/2002 concerning the Assessment of SOE Soundness Levels. The indicators used to measure the level of financial soundness are the return on equity (ROE), return on investment (ROI), cash ratio, current ratio, collection periods, inventory turnover, total asset turnover and equity to total assets ratio. PT Waskita Karya (Persero) Tbk financial soundness level tended to decline, namely from A (sound) in 2018 and then decreased to BBB (less sound) in 2019.